2007
DOI: 10.1002/ibd.20022
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Epidemiology of Inflammatory Bowel Disease in Lebanon

Abstract: The prevalence of IBD in this representative Lebanese cohort falls in the intermediate range of that reported for white populations in Europe and North America. Future studies are needed to examine local risk factors, disease genotypes and phenotypes, and epidemiologic time trends. The psychosocial burden of IBD in Lebanon appears significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 35 publications
(48 reference statements)
4
35
0
1
Order By: Relevance
“…[6][7][8] The present study identified some different clinical characteristics of UC to that reported in white and Asian populations. In relation to demographic characteristics, the age of onset for UC (almost equally present in both sexes) and a high percentage of nonsmokers are similar to the reports in other countries.…”
Section: Discussionmentioning
confidence: 55%
“…[6][7][8] The present study identified some different clinical characteristics of UC to that reported in white and Asian populations. In relation to demographic characteristics, the age of onset for UC (almost equally present in both sexes) and a high percentage of nonsmokers are similar to the reports in other countries.…”
Section: Discussionmentioning
confidence: 55%
“…In Barbados, West Indies, among a population that is 90% black and of African descent, incidence rates were about 1/100,000 for CD and about 2/100,000 for UC, with prevalence of about 17/100,000 for CD and about 44/100,000 for UC [9]. A recent Lebanese study reported incidence rates of 1.4 for CD and 4.1 for UC, with prevalence rates of 53 and 106, respectively [10]. However, this study is from a small, selected group of patients enrolled in a private health maintenance organization.…”
Section: Worldwide Incidence and Prevalence Datamentioning
confidence: 94%
“…The diagnostic criteria we used allow the inclusion of both active and inactive cases. Although Table 3 The results of HLA-B27 and HLA-B51 in the studied population and comparison the results in the other regions in our country (% frequencies) Pirim (121) Uyar ( [40,[72][73][74] 0-0.8 [75] 0.06-0.54 [46-48, 54, 76] 0.1-6.3 [60,75] 0.49 [12] 0.120 0.114-0.126 IBD 0.20-0.42 [77,78] 0.31 [79] 0.16 [80] 0.3-0.5 [81][82][83] 0.035 0.032-0.037 Ps 1.17-4.20 [84][85][86][87][88] 0.67 [56,89] 0.424 0.414-0.434…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…PsA 0.02-0.42 [89][90][91][92] 0.01-0.1 [54] 0.08-0.12 [80,93] 0.050 0.047-0.053 BD 0.135 [94] 0.08-042 [2][3][4][5] 0.019 0. [50,110] 0.004-0.021 [111] 0.0004-0.03 [112,113] 0.011 0. our questionnaire included the same items for RA, the frequency 0.21% (ap) we report here is lower than that reported from Izmir (0.36%) (ap) [6].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%